Pengolahan Limbah Cair Tahu Menjadi Biogas Menggunakan Reaktor Biogas Portabel - Rajagukguk, Kardo (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
From the tofu production process. The waste generated by tofu industries can be divided into two types, i.e the solid waste and liquid waste. One effort to reduce the environmental damage due to tofu liquid waste from the processing of tofu is to make the tofu liquid waste into biogas. The effort to convert liquid waste from tofu factories into biogas reguires a biogas reactor.Â  The aim of this study was to design a biogas reactor with a size of 1 m3 (1000 Liters) by using materials and equipment that are very easily available in the market at an affordable price, to determine the pressure, pH value and the quality of the flame produced when the biogas is used as fuel gas stove. The method used in this study is an experimental method within 30 days. The results showed that biogas pressure increased with increasing time (days). Maximum pressure is reached on day 21, which is 12.2 kPa. The average pH value is 6.91. The temperature in the biogas reactor tends to be stable with an average temperature of 31oC. The color of the flame when the biogas from tofu liquid waste is used as a gas fuel for a large flame gas stove is still a mixture of blue and yellow. The utilization of tofu liquid waste into biogas is expected to reduce environmental pollution and make tofu liquid waste become a high economic value and environmentally friendly.